A case report on the importance of imaging in the diagnosis of Lipofibromatous Hamartoma of the median nerve - Luis Adiel Medrano-Danes (Iberoamerican Journal of Medicine, 2020)
This case report presents a lipofibromatous hamartoma of the median nerve in a 31-year-old man who presents local deformity and a sensory deficit in the nerve territory. The tumor was evaluated with magnetic resonance, computed tomography, and plain film radiography, studying the pathognomonic findings of this tumor. The patient did not want surgical treatment because of prior surgical sequelae. A prior surgical biopsy was reported as a peripheral nerve with normal axonal fascicles surrounded by abundant fibroadipose tissue. This tumor has a low incidence with less than 180 cases reported in the literature.